Hullámverés: Terjedési folyamatok a médiában - Fokasz, Nikosz; Fokasz, Oresztész (Szociológiai Szemle, 2024)
The logistical function has been known and used by scientist for more than hundred years for mathematical description of progresses. Different diffusion processes, such as the spread of contagious diseases or inventions show logistical growth as well. On basis of these, we targeted to reveal the signs of logistical growth on some specific area of the press. For this purpose we have chosen the recently most spectacular and well-defined public discussion, and examined how the press reacted to the announcement made at Christmas in 2003 in the radio channel called “Tilos Radio” where one of the participant declared that he “would liquidate all Christians”. We consider our research as an attempt to contribute to the interpretation of certain communication models and to provide some hypothesis for further development. First of all, we collected all relevant articles from the leading Hungarian daily press. In align with our expectation, the evolution in time of the number of articles published reminds us strongly of the typical S-curve of the logistical growth. Upon specifying our criteria, it turned out that publishing occurred in several waves, mainly in three main, well-differentiated categories. After such differentiation, we tried to apply the logistical function on these three categories mentioned. The structure of these diagrams provided us with important information concerning the publication strategy of the newspapers concerned. The most surprising and therefore the most important conclusion of our investigation is, that only in one out of the three categories did we get to see the complete S-curve on the empirically applied logistical function. To be able to get a complete S-curve on the other categories as well, we should have implied that the investigated event had been only a later part of a stream started long before in time. Of course, it would be a paradox to state that the “Tilos Radio”-case has started long before the announcement has been made in “Tilos Radio”. Therefore, the result shows that the press operates in a kind of state of emergency. Daily press behaves in case of some certain topics like a close-wound spring. In such cases even a small act could trigger strong reactions. By using our method, we could measure and therefore, compare the state of emergency in the press.